Efektivitas Penerapan Metode Hiwar dan Kisah terhadap Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti Peserta Didik Kelas V SDN Pannyangkalang Kecamatan Bajeng Kabupaten Gowa - Nurafni; Usman; Rusmin B, Muhammad (Primer Edukasi Journal, 2024)
This research discusses the effectiveness of the application of the hiwar method and the story on the learning outcomes of Islamic Religious Education and Character for the fifth grade students of the Pannyangkalang State Elementary School. The objectives of this research are to: 1) Describe the learning outcomes of Islamic Religious Education and Character through the application of the hiwar method for fifth graders at the Pannyangkalang State Elementary School, 2) Describe the learning outcomes of Islamic Religious Education and Character through the application of the story method for fifth graders at the Pannyangkalang State Elementary School, and 3) Analyzing the effectiveness of the application of the hiwar method and the story on the learning outcomes of Islamic Religious Education and Character for the fifth grade students of the Pannyangkalang State Elementary School. The type of research used is a quasi-experimental. The population in this research were all students of the Pannyangkalang State Elementary School, totaling 170 students with a sample, namely class V, totaling 30 students. The sampling technique is purposive sampling. The results of the descriptive analysis showed that the average value of the learning outcomes of students who were taught using the hiwar method was 81.20 indicating the high category and those using the story method of 86.47 also indicating the high category. Based on the results of statistical analysis for learning outcomes, it shows that the tcount obtained is 3,065 and ttable is 2,048, so tcount > ttable. This shows that the application of the hiwar and story methods effectively improves the learning outcomes of Islamic Religious Education and Character for the fifth grade students of the Pannyangkalang State Elementary School.